Percy Jackson's : Greek Gods - Riordan, Rick; Rocco, John (Los Angeles : Disney-Hyperion, 2016)
"In Percy Jacksons Greek Gods, the son of Poseidon adds his own magic--and sarcastic asides--to the classics and gives readers his personal take on a whos who of the ancients, from Apollo to Zeus. If you like lots of lying, stealing, backstabbing, and cannibalism, then read on, because it definitely was a Golden Age for all that. Whether you are new to Greek mythology or well versed in it, this highly entertaining volume will make the ancient stories both relevant and impossible to forget"--Page 4 of cover.
Accelerated Reader
Keywords: Gods; Folk tales; Myth anthologies; Fiction; Juvenile works